FTIR spectroscopic studies with thermo acoustical parameters in binary and ternary liquid mixtures of amino acid and saccharide in aqueous medium - Rupesh Kumar Pradhan; Sulochana Singh (BMC Chemistry)
Abstract The interactions between amino acids and saccharides in aqueous environments are fascinating and have significant implications for various fields. These interactions can provide valuable insights into physiological processes, drug targeting, and delivery systems. To comprehend the synergy between saccharide (l-arabinose $$/$$ / d-xylose) and non-essential amino acid (l-aspartic acid; Asp) in an aqueous system, ultrasonic velocity ( $$U$$ U ) at 293.15 K–313.15 K (with 5 K interval) and at experimental pressure P = 101 kPa were measured using a digital ultrasonic interferometer. The solution density, $$\uprho$$ ρ and the propagation of sound waves through the experimental solutions are directly correlated with the weak and strong molecular interactions that take place between the solution’s constituents. $$\uprho$$ ρ and $$U$$ U data was utilised to compute the following acoustic parameters isentropic compressibility $${K}_{s}$$ K s , apparent molar isentropic compressibility $${\text{K}}_{{{\text{s}},\upphi }} ,$$ K s , ϕ , free volume $${V}_{f}$$ V f , free length $${L}_{f}$$ L f , internal pressure $${π }_{i}$$ π i , acoustic impedance $$Z$$ Z , surface tension $$γ$$ γ and relative association $${R}_{A}$$ R A . Positive $${\text{K}}_{\text{s}}^{0}$$ K s 0 values make ion–solvent interactions stronger than ion-ion interactions. Positive values of $${\text{K}}_{{{\text{s}},\upphi ,{\text{ tr}}}}^{0}$$ K s , ϕ , tr 0 imply greater interactions between the polar segments of l-arabinose/d-xylose and the zwitterionic groups of Asp. The solvation mechanisms of Asp result in the reconstruction of the water structure. The FTIR technique was used to verify the results of the acoustic study. The presence of intermolecular hydrogen bonding and intramolecular hydrogen bonding is shown by the broadening of the absorption band. The system under research exhibits predominant ion-hydrophilic $$/$$ / hydrophilic interactions as confirmed by FTIR analysis. Understanding how Asp in aqueous environment interacts with saccharides such as l-arabinose and d-xylose might help one better understand how these molecules behave in biological systems.